The Vistula, Overgrown Shrubs, and Untended Gardens in the Literature of Postwar, Communist Warsaw - Barcz, Anna (Porównania, 2023)
The article offers to combine the environmental history and memory of Warsaw on the example of analyses of literary works relating mainly to the post-1939-war and communist periods. These references involve specific places, such as the Vistula River, wastelands and abandoned allotments. In addition to brief exemplifications from Marek Hłasko and Dorota Masłowska, the psychogeographical interpretation of the environmental realities of post-war Warsaw in the People’s Republic of Poland was developed in the more detailed analysis of three novels by Tadeusz Konwicki: A Minor Apocalypse, Underground River, Underground Birds and Ascension. It turned out that the traumatic history of the city, which has not been recognized so clearly in the environmental sense, is applicable in the analysis of these novels and by greening the undeveloped wastelands.